Corporate Governance, Financial Performance, and Sustainability Disclosure - Alya Salma Zahrani; Ajeng Tita; Bima Rafly Fachrezzi (Journal of Accounting Science, 2026)
General Background: The disclosure of sustainability reports has become a critical aspect of modern business practices as it reflects a company’s commitment to sustainability, transparency, and social responsibility. Specific Background: In the mining sector, particularly among companies listed on the Indonesia Stock Exchange (IDX), sustainability reporting has received greater attention during the 2020–2023 period due to increasing stakeholder demands for ESG transparency. Knowledge Gap: However, few studies have examined the influence of profitability, firm size, firm activities, audit committees, and boards of directors on sustainability report disclosures in Indonesian mining companies. Objective: This study aims to analyze the influence of profitability, firm size, firm activities, audit committees, and boards of directors on sustainability report disclosures. Method: This quantitative study uses panel data from 33 mining companies selected through purposive sampling. Data were analyzed using panel regression with EViews 12, while model selection was performed using the Chow and Hausman tests. Results: The findings indicate that firm size and the audit committee have a positive and significant effect on sustainability report disclosure, whereas profitability, firm activities, and the board of directors do not have a significant effect. Novelty: This study combines financial performance and corporate governance variables to provide empirical evidence from Indonesian mining companies. Implications: Companies should strengthen the effectiveness of their audit committees and maintain consistent sustainability reporting practices.